2019
DOI: 10.1136/gutjnl-2018-317556
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prediction rule for estimating gastric cancer risk in the Chinese high-risk population: a nationwide multicentre study

Abstract: ObjectiveTo develop a gastric cancer (GC) risk prediction rule as an initial prescreening tool to identify individuals with a high risk prior to gastroscopy.DesignThis was a nationwide multicentre cross-sectional study. Individuals aged 40–80 years who went to hospitals for a GC screening gastroscopy were recruited. Serum pepsinogen (PG) I, PG II, gastrin-17 (G-17) and anti-Helicobacter pylori IgG antibody concentrations were tested prior to endoscopy. Eligible participants (n=14 929) were randomly assigned in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
138
0
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(163 citation statements)
references
References 50 publications
8
138
0
17
Order By: Relevance
“…Non‐invasive serological screening combined with endoscopy can help improve the effect of gastric cancer screening . A total of 14 929 serum samples and endoscopic data from China showed that age, sex, pepsin ratio < 3.89, gastrin‐17 > 1.50 pmol/L, H. pylori antibody positive, salted food, and fried food are the seven high‐risk factors for gastric cancer . The gastric cancer risk score scale was developed based on these factors and has been used for the screening of populations at high risk for gastric cancer in China…”
Section: Helicobacter Pylori Screening and Eradication Strategymentioning
confidence: 99%
“…Non‐invasive serological screening combined with endoscopy can help improve the effect of gastric cancer screening . A total of 14 929 serum samples and endoscopic data from China showed that age, sex, pepsin ratio < 3.89, gastrin‐17 > 1.50 pmol/L, H. pylori antibody positive, salted food, and fried food are the seven high‐risk factors for gastric cancer . The gastric cancer risk score scale was developed based on these factors and has been used for the screening of populations at high risk for gastric cancer in China…”
Section: Helicobacter Pylori Screening and Eradication Strategymentioning
confidence: 99%
“…26,27 Picked food and salty food intake frequently were positively correlated with PL, while vegetable intake frequently was associated with a lower risk of GCPL, and evidence of this relationship has been provided in some risk factors studies. [27][28][29][30] Mental trauma history of participates containing major accidental bodily injury, seriously ill or dies of close relatives, threats of violence et al, may cause easily some physical problems, which push them to see doctors or take physical examination, thus they accepting early treatment or interventions for bad living habits to prevent GCPL and acting as a protective factor. Participations with atrophic gastritis history had higher risk of UCPL.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent multicentre cross-sectional study, a predicted model of GC was developed and validated involving serology biomarkers (pepsinogen I, pepsinogen II, anti-Helicobacter pylori antibody, and gastrin-17) with the C-index value of 0.76. 29 But based on hospital opportunistic screening, it would be limited for applying in population screening. Therefore, our next research goal is taking these serology biomarkers applied in our predicted model for targeting the high-risk UGC population to improve the model accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that a gastric cancer prediction tool based on a panel of serum biomarkers including PG I, PG II, gastrin-17 (g-17) and anti-H. pylori IgG antibody had good performance in identifying high-risk patients. 72 Huang et al 73 further found that serum TFF3 levels were significantly higher in patients with gastric cancer than in their control group, and suggested that the combined detection of serum PG and TFF3 could improve the efficacy of gastric cancer screening. Similarly, Aikou et al 74 found that serum TFF3 levels in patients with gastric cancer were significantly higher than those in the normal group.…”
Section: Diagnosis Of Antralization and Its Implications In Clinical mentioning
confidence: 98%